Highly anisotropic black phosphorous-graphene hybrid architecture for ultrassensitive plasmonic biosensing: Theoretical insight. (22nd February 2018) - Yuan, Yufeng; Yu, Xiantong; Ouyang, Qingling; Shao, Yonghong; Song, Jun; Qu, Junle; Yong, Ken-Tye
Abstract: This study proposed a novel highly anisotropic surface plasmon resonance (SPR) biosensor employing emerging 2D black phosphorus (BP) and graphene atomic layers. Light absorption and energy loss were well balanced by optimizing gold film thickness and number of BP layers to generate the strongest SPR excitation. The proposed SPR biosensor was designed by the phase-modulation approach and is more sensitive to biomolecule bindings, providing 3 orders of magnitude higher sensitivity than the red-shift in SPR angle. Our results show the optimized configuration was 48 nm Au film coated with 4-layer BP crystal to produce the sharpest phase variation (up to 89.8975°), and lowest minimum reflectivity (1.9119 × 10 −7 ). Detection sensitivity up to 7.4914 × 10 4 degree/refractive index unit is almost 4.5 times enhanced compared to monolayer graphene-based SPR sensors with 48 nm Au film. The anisotropic BP layers act as a polarizer, so the proposed SPR biosensor would exhibit optically tunable detection sensitivity, making it a promising candidate for exploring highly anisotropic platforms in biosensing.